PENGELOLAAN KESAN KOMIKA STAND UP COMEDY PADA KOMUNITAS STAND UP INDO PEKANBARU - Denny Aprianto Vijay Lubis; Nova Yohana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Stand up comedy has become a new interest in the world of art, especially comedy in Indonesia. Stand up comedy gives freedom to the person to talk about and do anything, so that a comic has his own way to make the audience interested and entertained. This study aims to determine the front stage, middle stage, and back stage comic in Pekanbaru city. This study uses qualitative research methods using dramaturgy studies. The informant of the study consisted of six people, consisting of three main informants and three supporting informants. Data collection techniques are conducted by interview, observation, and documentation. Data analysis techniques use the Miles and Huberman interactive models in the form of data collection, data reduction, data presentation, and conclusion drawing. The results of the study indicate that the appearance of a comic when on stage is the result of managing an impression that is designed in such a way as to the demands of the profession being pursued. Front stage is a display full of settings. An ideal concept that someone wants to display in accordance with the expectations of society. As a stand up comedian, the comic look for a "persona" as their identity when on stage and at the same time as a differentiator from other comic. The middle stage is the transition area of the comic from the back stage to the front stage. On this middle stage, comic conducts various kinds of activities to prepare everything that can support her appearance while on the front stage. Starting from the preparation of material consisting of writing, combud, open mic, and rewrite until build a mood before appearing as comic. On back stage they can show their original status without having to cover it up. There is nothing on this stage that they cover up and act like an ordinary person who has normal, emotional, and not always makes others laugh.